“Evaluación de impactos ambientales de la industria porcina y propuestas de mejora en el manejo de purines” - Peralta Cabezas, Daniela Magdalena (2023)
The present work consisted of a bibliographical study about the evaluation of environmental impacts within the swine industry and proposals for improvement in the management of manure, which affect public health due to the greater increase in diseases.The objective of this document is to identify the causes and problems generated by pig production and list the proposals for improvement in the management of slurry in order to reduce the degradation that they cause to the planet by affecting the soil, air and water. The methodology with which this work was carried out is by the inductive-deductive method, through scientific articles and among others. Currently, it is considered that pig productions due to bad pig practices are the ones that cause a greater increase in contamination due to the increase in carbon dioxide and methane gas due to small and medium producers, since they have been named as the main authors of the increase in environmental problems and this will generate an increase in the proliferation of infectious vector organisms. Based on the results obtained, I have come to the conclusion that pig farmers can carry out improvement proposals such as the development of biodigesters and using biogas or organic fertilizers such as composting or bocashi for agricultural crops. In addition, it is recommended to use meshes and doors in order to reduce the presence of infectious vectors.